Evaluasi Karakter Agronomi Beberapa Calon Varietas Paria (Momordica Charantia L.) Sebagai Dasar Seleksi Varietas Unggul - Arfian Faqih Rahmani; Sari Megawati; Asih Farmia (University of Prof. Dr. Hazairin, SH, 2026)
Bitter gourd (Momordica charantia L.) is a horticultural crop with high potential for development through breeding of high-yielding varieties. This study aimed to evaluate agronomic characteristics and yield potential of the bitter gourd hybrid candidate PRBI001 compared with three check varieties, namely YSPA 095, MC 2604, and PJHL 912. The research was conducted at PT Dinasty Inti Agrosarana, Banguntapan District, Bantul Regency, Special Region of Yogyakarta, from December 2025 to April 2026. A non-factorial randomized complete block design (RCBD) was used with four varieties and four replications. Each plot consisted of 40 plants with 12 sampled plants per plot. Data were analyzed using analysis of variance (ANOVA) at the 5% significance level, followed by Honest Significant Difference (HSD) test at 5% using PKBT-STAT 3.2 software. The results showed that variety had significant to highly significant effects on several agronomic traits, with a coefficient of variation ranging from 0.25% to 9.71%. PRBI001 exhibited superior performance in leaf width (18.66 cm), fruit length (33.14 cm), flesh thickness (1.06 cm), fruit weight (337.30 g), fruit weight per plant (3.53 kg plant⁻¹), fruit weight per plot (121.87 kg plot⁻¹), yield (62.81 ton ha⁻¹), and 1000-seed weight (197.96 g). These traits can be used as priority selection criteria in breeding programs. Overall, PRBI001 shows strong potential to be developed as a superior bitter gourd hybrid variety with high yield performance.